2011
DOI: 10.1093/pubmed/fdr087
|View full text |Cite
|
Sign up to set email alerts
|

Weight change during and after Ramadan fasting

Abstract: Observers of Ramadan lose on average about a kilogram of weight over 4 weeks, and the lost weight is quickly regained. Current weight management treatments generally assume that skipping meals leads to weight gain and advise against it. The finding suggests that further research is needed on the justification of the 'do not skip meals' advice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
58
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(65 citation statements)
references
References 26 publications
3
58
0
4
Order By: Relevance
“…This is an expected result as most studies regarding BMI changes in Ramadan have shown significant reduction. 14,15 The systolic and diastolic pressures in both groups had reduced too. Although the reduction was not statistically significant, this is also expected as BMI and blood pressure has an established linear association.…”
Section: Discussionmentioning
confidence: 93%
“…This is an expected result as most studies regarding BMI changes in Ramadan have shown significant reduction. 14,15 The systolic and diastolic pressures in both groups had reduced too. Although the reduction was not statistically significant, this is also expected as BMI and blood pressure has an established linear association.…”
Section: Discussionmentioning
confidence: 93%
“…12 Literature search suggested that it is in fact not known whether Ramadan fasting generates weight loss or weight gain. 10 Only a small number of studies were identified, which used small samples, mostly of students and pregnant women, and reported inconsistent results: one found weight gain, 13 three reported weight loss, [14][15][16] and five found no significant weight change. 12,[17][18][19][20] In order to investigate this further we took weight measurements in 202 Ramadan observers at baseline, at the end of Ramadan, and a month later.…”
Section: Discussionmentioning
confidence: 99%
“…Ramadan generated a weight loss of about 1 kg, which was re-gained within the next four weeks. 10 Correlational studies that link weight gain and being overweight with skipping meals, 21,22 have led to weight management programmes commonly suggesting that skipping meals undermines weight loss or generates weight gain, while regular spacing of food intake can help. [1][2][23][24][25] This is probably incorrect.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have demonstrated that persistent fasting during the month of Ramadan resulted in mild weight loss but this reverted back to normal after Ramadan is over [10]. Another recent trial that evaluated the effect of fasting on weight, blood pressure and total cholesterol in hypertensive patients has shown no change in total cholesterol but improvement in blood pressure and weight [11].…”
Section: Discussionmentioning
confidence: 99%